The Actualization of Service for the Nation KH. Ikhwanul Faruq Through the Role of Islamic Boarding Schools Darul Hidayah Uman Agung - Aminul Qodat; Ikhwan Aziz (Journal of Research in Islamic Education, 2021)
Abstract Pesantren is an important institution in Indonesia to build the character of generations. Islamic boarding school character education teaches its students to socialize and unite among the nation's children throughout the archipelago, regardless of ethnicity, background and religion. They are taught to interact harmoniously among the various communities of the nation. If there is a dispute, they are asked to make peace through the mediation of the pesantren clerics or who are appointed by the pesantren people to play the mediation function. Kyai figures who are controlled in the process of Islamic learning activities at this institution are the key to the success of the pesantren. Kyai's leadership model is charismatic leadership with an exemplary spirit, where the Kyai figure is seen by the community as an expert in the field of religion, considered capable of providing solutions in the social and religious fields, as well as being able to contribute to the nation in building the young generation marked by the expansion of national education goals. Character education is what Kyai is including sincerity education, independence education, brotherhood education and discipline education. All the process of building this character is done on the basis of example. That is what Kyai teaches is the knowledge that has been exemplified before. With an exemplary spirit in educating students, we can see that every graduate boarding school has a character similar to their Kyai. independence education, brotherhood education and discipline education. All the process of building this character is done on the basis of example. That is what Kyai teaches is the knowledge that has been exemplified before. With an exemplary spirit in educating students, we can see that every graduate boarding school has a character similar to their Kyai. independence education, brotherhood education and discipline education. All the process of building this character is done on the basis of example. That is what Kyai teaches is the knowledge that has been exemplified before. With an exemplary spirit in educating students, we can see that every graduate boarding school has a character similar to their Kyai.